Efficacy of extended focused assessment with sonography for trauma using a portable handheld device for detecting hemothorax in a low resource setting; a multicenter longitudinal study - Kithinji, Stephen Mbae; Lule, Herman; Acan, Moses; Kyomukama, Lauben; Muhumuza, Joshua; Kyamanywa, Patrick (BMC Medical Imaging, 2022)
Introduction: Chest trauma is one of the most important and commonest injuries that require timely diagnosis, accounting for 25–50% of trauma related deaths globally. Although CT scan is the gold standard for detection of haemothorax, it is only useful in stable patients, and remains unavailable in most hospitals in low income countries. Where available, it is very expensive. Sonography has been reported to have high accuracy and sensitivity in trauma diagnosis but is rarely used in trauma patients in low income settings in part due to lack of the sonography machines and lack of expertise among trauma care providers. Chest X-ray is the most available investigation for chest injuries in low income countries. However, it is not often safe to wheel seriously injured, unstable trauma patients to X-ray rooms. This study aimed at determining the efficacy of extended focused assessment with sonography for trauma (eFAST) in detection of haemothorax using thoracostomy findings as surrogate gold standard in a low resource setting. Methods: This was an observational longitudinal study that enrolled 104 study participants with chest trauma. Informed consent was obtained from all participants. A questionnaire was administered and eFAST, chest X-ray and tube thoracotomy were done as indicated. Data were analysed using SPSS version 22. The sensitivity, specificity, predictive values, accuracy and area under the curve were determined using thoracostomy findings as the gold standard. Ethical approval for the study was obtained from the Research and Ethics Committee of Kampala International University Western Campus REC number KIU-2021-53. Results: eFAST was found to be superior to chest X-ray with sensitivity of 96.1% versus 45.1% respectively. The accuracy was also higher for eFAST (96.4% versus 49.1%) but the specificity was the same at 100.0%. The area under the curve was higher for eFAST (0.980, P = 0.001 versus 0.725, P = 0.136). Combining eFAST and X-ray increased both sensitivity and accuracy. Conclusion: This study revealed that eFAST was more sensitive at detecting haemothorax among chest trauma patients compared to chest X-ray. All patients presenting with chest trauma should have bedside eFAST for diagnosis of haemothorax
Keywords: eFast; Hemothorax; Efficacy; X-ray